Isolation and Identification of Phenolic Compounds by HPLC and Electrospray Ionization Mass Spectrometry and their Free Radical Scavenging Activity of Shorea tumbuggaia Roxb. - Sade Ankanna; N Savithramma (International Journal of Phytomedicine, 2013)
The impetus for developing analytical methods for phenolic compounds in natural products has proved to be multifaceted. The traditional usage of Shorea tumbuggaia as a folklore medicine, the plant parts are administered to counteract different ailments. Hence the present study intended to isolate phenolic compounds from stem bark of Shorea tumbuggaia by using 70% acetone and poly vinyl poly pyrrolidone; and characterized by U.V. Visible spectrometry, High performance liquid chromatography/ electrospray ionization mass spectrometry. And an assessment of the ability of the extracted phenols to scavenge the hydrozen perioxide; sueproxide, DPPH was determined with reference to ascorbic acid by spectrophotometric methods. Total 90 phenolic compounds were obtained at both positive and negative ion modes of LCMS. Among the isolated phenols, 20 phenolic compounds have been identified based on their retention time and m/z values. Namely, Benzoic acid, caffeoyl-5-ferryol quinic acid, thymol, homovanillic acid, eudesmic acid, caffeic acid, 9 CoA, chrysin, pinocembrin, luteolin, quercetin-3-rutinoside, ellagic acid, cohumulone, caffeic acid hexoside, lupulone, deoxy hexoside of ellagic acid, 3’-4-Di hydroxyl 5-6 dimethoxy 7-0-glucoside flavones, oleuropein, pelargonidin-3-rutinoside and heptameric procyanidin. These phenols has showed good antioxidant activity the highest hydrogen peroxide (H2O2) radical scavenging effect of the isolated phenolic compounds has been recorded at 81.8% when compared to the DPPH and superoxide ion activities with reference to ascorbic acid. This study illustrate the rich array of phenolic compounds and their free radical scavenging activity of stem bark of Shorea tumbuggaia could be utility as health beneficial bioactive compounds.